Kecernaan Serat Kasar dan Lemak Kasar Babi Grower yang diberi Ransum Mengandung Silase Limbah Sawi Putih (Brassica pekinensia L) - Amheka, Zakarias Marsel; Dodu, Tagu; Suryani, Ni Nengah; Sembiring, Sabarta (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of this study was to determine the effect of using chicory (Brassica pekinensis L) waste silage in rations on the consumption and digestibility of crude fiber and crude fat of grower pigs. The livestock used were 12 landrace pigs in the grower aged 3-4 months with initial body weights ranging from 29-52 kg and an average of 36 kg (CV = 17.72%). This study used a randomized block design (RBD) which consisted of 4 treatments and 3 replications so that there were 12 experimental units. The treatment used was R0: 100% basal ration, R1: 90% basal ration + 10% chicory waste silage, R2: 85% basal ration + 15% chicory waste silage and R3: 80% basal ration + 20% waste silage Chinese cabbage. The variables studied were consumption and digestibility of crude fiber and crude fat. The results showed that the treatment had no significant effect (P>0.05) on consumption and digestibility of crude fiber and crude fat. It was concluded that the use of chicory waste silage (Brassica pekinensis L) at levels of 10%, 15% and 20% had the same effect on consumption and digestibility of crude fiber and crude fat in grower phase pigs.